2016
DOI: 10.1371/journal.pone.0163644
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Increase in Serum Low-Density Lipoprotein Cholesterol Concentration during Hepatitis C Interferon-Free Treatment

Abstract: Background & AimWe performed lipid analyses at the early period of therapy in patients with chronic hepatitis C who underwent interferon (IFN)-free direct-acting antiviral (DAA) treatment, and we attempted to identify the factors that contributed to a rapid increase in the patients’ serum low-density lipoprotein cholesterol (LDL-C) concentration.MethodsWe retrospectively analyzed the cases of 100 consecutive patients with HCV infection treated at the National Hospital Organization Nagasaki Medical Center: 24 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
81
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 35 publications
15
81
0
Order By: Relevance
“…Upon treating CHC genotype 1 patients, Hashimoto et al [18] observed a rapid increase in LDLc and TC during the first 28 days of treatment that was stronger in patients who received LDV/SOF than in those who received daclatasvir/sunaprevir (DCV/ASV), while Endo et al [19] reported a significantly greater increase in TC and LDLc in the SOF/LDV group than in the DCV/ASV group during treatment, but at 4 and 12 weeks after therapy, the serum levels of TC and LDL-c were similar in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Upon treating CHC genotype 1 patients, Hashimoto et al [18] observed a rapid increase in LDLc and TC during the first 28 days of treatment that was stronger in patients who received LDV/SOF than in those who received daclatasvir/sunaprevir (DCV/ASV), while Endo et al [19] reported a significantly greater increase in TC and LDLc in the SOF/LDV group than in the DCV/ASV group during treatment, but at 4 and 12 weeks after therapy, the serum levels of TC and LDL-c were similar in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the increases in cholesterol levels during treatment were dependent on the treatment regimen[22]. Although the increases in TC and LDL-C levels were features of both DCV + ASV and SOF + LDV treatment, the increase in cholesterol during treatment was much greater in the SOF + LDV-SVR group than in the DCV + ASV-SVR group[22].…”
Section: Discussionmentioning
confidence: 99%
“…Although the increases in TC and LDL-C levels were features of both DCV + ASV and SOF + LDV treatment, the increase in cholesterol during treatment was much greater in the SOF + LDV-SVR group than in the DCV + ASV-SVR group[22]. The differences in the increase in cholesterol between DCV + ASV-SVR and SOF + LDV-SVR groups may not be simply explained by cancellation of disturbed lipid metabolism caused by HCV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations